The Ubiquitin Ligase TRIP12 Limits PARP1 Trapping and Constrains PARP Inhibitor Efficiency - Gatti, Marco; Imhof, Ralph; Huang, Qingyao; Baudis, Michael; Altmeyer, Matthias (Cell reports (Cambridge), 2020)
PARP inhibitors (PARPi) cause synthetic lethality in BRCA-deficient tumors. Whether specific vulnerabilities to PARPi exist beyond BRCA mutations and related defects in homology-directed repair (HDR) is not well understood. Here, we identify the ubiquitin E3 ligase TRIP12 as negative regulator of PARPi sensitivity. We show that TRIP12 controls steady-state PARP1 levels and limits PARPi-induced cytotoxic PARP1 trapping. Upon loss of TRIP12, elevated PARPi-induced PARP1 trapping causes increased DNA replication stress, DNA damage, cell cycle arrest, and cell death. Mechanistically, we demonstrate that TRIP12 binds PARP1 via a central PAR-binding WWE domain and, using its carboxy-terminal HECT domain, catalyzes polyubiquitylation of PARP1, triggering proteasomal degradation and preventing supra-physiological PARP1 accumulation. Further, in cohorts of breast and ovarian cancer patients, PARP1 abundance is negatively correlated with TRIP12 expression. We thus propose TRIP12 as regulator of PARP1 stability and PARPi-induced PARP trapping, with potential implications for PARPi sensitivity and resistance. [Display omitted] •TRIP12 is a PAR-targeted ubiquitin ligase (PTUbL)•The HECT and WWE domains of TRIP12 cooperate to mediate PARP1 turnover•TRIP12 loss sensitizes cancer cells to PARP inhibitors in a PARP1-dependent manner•TRIP12 status may help to estimate how cancer cells respond to PARP inhibition Gatti et al. demonstrate that the enzyme TRIP12 is a PAR-targeted ubiquitin ligase (PTUbL), which regulates PARP1 turnover. TRIP12 and PARP1 are inversely correlated in human cancers, and loss of TRIP12 leads to increased PARP inhibitor-induced PARP trapping, replication-associated DNA damage, and amplifies PARP inhibitor-induced cancer cell death.